Suspected testicular torsion in children: diagnostic dilemma and recommendation for a lower threshold for initiation of surgical exploration - Tariq O Abbas (18090619) (2018)
Purpose Testicular torsion (TT) represents a clinical challenge that needs emergency surgical assessment. It is common to have negative scrotal exploration due to confounding symptoms and signs which makes it sometimes difficult to differentiate from similar surgical emergencies that do not warrant surgery. At the same time, several occasions of misdiagnoses or late interventions occur with devastating effects. We aim at delineating the significance of the different clinical, laboratory, and radiological variables in the detection of TT. Methods We retrospectively reviewed the charts of 52 patients who were surgically explored with a preoperative working diagnosis of suspected TT in our center over the period from 2011 to 2015. All the patients were examined by pediatric surgeons in the emergency room and had undergone ultrasound imaging of the testes. The ultrasound images were retrospectively reviewed by a pediatric radiologist who was blinded to the intraoperative findings. Univariate and multivariate and logistic regression analyses were performed. Results Of the studied group of patients, the majority (84.6%) had TT upon surgical exploration. The most frequently presented symptom was pain (80.8%), and only a minority (11.5%) presented with vomiting. Radiological findings with the highest sensitivity were heterogeneous echogenicity in favor of TT and enlarged epididymis indicating that TT is unlikely. However, the predictability of TT by any of the assessed clinical and imaging factors was statistically insignificant. Conclusion It is important to gather all relevant data from clinical, laboratory, and imaging sources when assessing pediatric patients with suspected TT given the inaccuracy of each single one of them if used alone. Keeping this in mind, Doppler ultrasound has a significant role to aid in the accuracy of the diagnosis and hence the appropriate decision-making thereafter. However, we found no single clinical or imaging sign that is sensitive enough to prove or rule out TT. Therefore, surgical exploration should take place in a timely manner. Moreover, further research is necessary to construct scoring systems where different predictors collectively have higher reliability. Other Information Published in: Research and Reports in Urology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/rru.s186112